Identity development and belonging of first nations women from Georgina Island - Carolynne Warton (10854354) (2010)
This study explores the effects of the Indian Act and Bill C-31 on the identity development and sense of belonging felt by women from Georgina Island First Nation. The purpose of this study is to give voice to the First Nations women from Georgina Island whose identity and lives have been impacted by this legislation. The framework and methodology that guided this research was respectful of the indigenous knowledge and traditions of this community. The vision of the community and the participants was the most important focus of this study. The sharing which took place provided insight into the how it felt for the women to have their identity removed by the Canadian Government, the challenges that the removal created within the community, what it felt like to have that identity 'given' back, how important community is and what these women wish for our future generations.